Reinforcing Business Resilience Through Entrepreneurial Competencies During Pandemic COVID-19: A Case of Indonesian MSMEs - Rozan Hanifan; Wawan Dhewanto (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2022)
Although research on entrepreneurial competencies has been widely carried out in the last decades, this topic is still preliminary. Indonesian MSMEs have been severely impacted by COVID-19, with losses of up to millions. Entrepreneurial competencies are believed to be the main driver in handling this issue. Underlined by the disaster and crisis management theory, entrepreneurial competencies are expected to give a company both long-term adaptability and innovation abilities that may result in significant improvements in their business as well as the short-term coping capacity to recover from violent shocks. Thus, this study builds a novel conceptual framework that determines the influence of entrepreneurial competencies on business resilience in the Indonesian MSMEs context. Several mediator variables were also included in the conceptual model: dynamic capability and innovation ambidexterity. Through purposive sampling, a sample of 220 Indonesian MSME actors get involved in this study. PLS-SEM procedure through a two-stage approach was used to test the proposed model. The results show that entrepreneurial competencies significantly impact business resilience in Indonesian MSMEs. It was also found that dynamic capabilities and innovation ambidexterity partially mediated those relationships. From these results, this study suggests that business practitioners should become more aware of their competencies to survive in this uncertain world. In addition, the government must re-educate and ensure that all middle and lower entrepreneurs have appropriate competencies to continue to compete. Keywords:   Entrepreneurial Competencies; Business Resilience; Dynamic Capability; Innovation Ambidexterity; Indonesian MSMEs